Indonesia Pengaruh Independensi Auditor, Kompleksitas Tugas, Pemahaman Good Governance, Ketidakjelasan Peran Terhadap Kinerja Auditor - Maria Tokan Ina Surat (JURNAL EKOBIS DEWANTARA, 2018)
Auditor performance is an action or execution of inspection tasks that have been completed by the auditor within a certain time. The performance of an auditor is seen from several factors that cause an increase or decrease in auditor performance. This study aims to examine the influence of auditor independence, task complexity, good governance understanding, and unclear role on the performance of auditors. To test the hypothesis used primary data by using purposive sampling method. Data analysis techniques use multiple linear regression analysis with auditor's performance as dependent variable (Y) and auditor independence, task complexity, good governance understanding, unclear role as independent variable (X). After the data were analyzed it was found that the auditor independence variable had a positive effect on the auditor's performance with the value of t arithmetic> t table 3,411> 2,021 and the significance value equal to 0.001. The task complexity variable has a negative effect on the auditor's performance with the value of t arithmetic <t table -3.250 <2.021 and the significance value of 0.002. The variable of good governance understanding has a positive effect on auditor performance with t value> t table 2,203> ​​2,021 and its significance value is 0,033. The role unclear variable has a negative effect on auditor performance with t value <t table -2,207 <2,021 and its significance value is 0,033.